2019
DOI: 10.1016/j.ijheatmasstransfer.2019.04.117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of transparent oscillating heat pipes filled with solar absorptive nanofluids

Abstract: Nanoparticle-based volumetric solar absorption has been shown to be an effective technique to realize efficient solar harvesting. However, most of such systems under study are 8 stationary and cannot realize solar energy transport, which limits their potential applications to a 9 large extent. A novel idea of using directive absorptive nanofluids in oscillating heat pipes (OHP) 10 is investigated in this work, which would achieve efficient solar energy capture and transportation 11 simultaneously without the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 51 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…The thermal resistance was as low as 0.0024 • C/W. Jin H et al [202] used transparent PHP with nano-fluids as the work medium for the collection and transmission of solar energy. The maximum energy conversion efficiency can reach 92%.…”
Section: Future Trendsmentioning
confidence: 99%
“…The thermal resistance was as low as 0.0024 • C/W. Jin H et al [202] used transparent PHP with nano-fluids as the work medium for the collection and transmission of solar energy. The maximum energy conversion efficiency can reach 92%.…”
Section: Future Trendsmentioning
confidence: 99%
“…The results showed that the use of nanofluid instead of water could lead to a reduction in start-up time. Jin et al [97] produced transparent-shaped OHPs and added nanofluids to them and studied the performance of the system. Thanks to the nanoparticles added to the system, radiation absorption has significantly increased and performance has improved.…”
Section: Nanofluid Applications In Heat Pipe Solar Collectorsmentioning
confidence: 99%
“…The effective multiplication factor was decreased in all nanoliquids; however, the effect varied according to the nanoparticle type. Jin et al [12] enhanced solar energy collection and conveyance by using a water-based Au (gold) and MWCNTs nanoliquid. A significant increase in energy absorption was seen when nanoparticles were added to water; as compared to pure water, MWCNTs nanoliquid harvests about 5.5 times more energy.…”
Section: Introductionmentioning
confidence: 99%